2019
DOI: 10.3390/su11113010
|View full text |Cite
|
Sign up to set email alerts
|

Improving Municipal Solid Waste Collection Services in Developing Countries: A Case of Bharatpur Metropolitan City, Nepal

Abstract: Municipal solid waste management is one of the major challenges that cities in developing countries are facing. Although waste collection services are critical to build a smart city, the focus of both scholarship and action/activism has been more on the utilization of waste than on collection. We devised a choice experiment to elicit the preferences of municipal residents with regard to the various attributes of solid waste collection services in the Bharatpur Metropolitan City of Nepal. The study showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 50 publications
0
51
0
2
Order By: Relevance
“…Appendix A provides more detailed information about the 56 studies including country/initiative studied, method of the study and the aims/objectives of the study. Geographical locations (country/continent) of the included studies by descending order (based on the number of studies identified) India [28,[32][33][34][35][36][37][38][39][40][41][42][43][44][67][68][69][70]79] China [45][46][47][48][49][50][51][52][53]71,76,80] Indonesia [54][55][56][57] Brazil [3,58,72] Malaysia [59][60][61] Vietnam [62,73] Mexico [63] Turkey [78] Egypt [81] Romania [64] Nepal [65] ...…”
Section: Study Contexts and Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…Appendix A provides more detailed information about the 56 studies including country/initiative studied, method of the study and the aims/objectives of the study. Geographical locations (country/continent) of the included studies by descending order (based on the number of studies identified) India [28,[32][33][34][35][36][37][38][39][40][41][42][43][44][67][68][69][70]79] China [45][46][47][48][49][50][51][52][53]71,76,80] Indonesia [54][55][56][57] Brazil [3,58,72] Malaysia [59][60][61] Vietnam [62,73] Mexico [63] Turkey [78] Egypt [81] Romania [64] Nepal [65] ...…”
Section: Study Contexts and Characteristicsmentioning
confidence: 99%
“…Despite advocating for the smart city agenda, some developing countries are still held back by the lack of investment in basic infrastructure. Basic urban infrastructure, such as having proper water drainage and sewerage systems, are requisite for any city to thrive, but some cities still face a shortfall in providing these services [37,43,65]. In India, smart city adoption is held back by the lack of provision and maintenance in basic infrastructure, which result in uneven development and lowquality infrastructure in some cities, particularly in the slum areas [43].…”
Section: Lack Of Investment In Basic Infrastructurementioning
confidence: 99%
See 3 more Smart Citations